2021
DOI: 10.1109/tnano.2021.3076663
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Dielectric Property Relationship in Polypropylene/Multi-Element Oxide Nanocomposites

Abstract: This paper reports on an investigation into the effects of different multi-element oxide nanofillers on the structure and dielectric properties of polypropylene (PP)-based nanocomposites. Magnesium aluminate (MgAl2O4), calcium carbonate (CaCO3) and surface-modified calcium carbonate (CaCO3T) have been added to the PP to determine their effects on thermal properties, structural changes, dielectric response and breakdown strength. The results show that PP nanocomposites containing MgAl2O4 possess lowered breakdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The tensile strength, Young’s modulus, and elongation at break initially increased and subsequently decreased as further addition of hybrid nanofillers to the XLPE matrix. It is reported in various studies that all samples of the nanocomposite have better tensile properties than unfilled XLPE [ 38 , 39 , 40 ]. This study ascertained an enhancement of tensile strength with increase in the LDH-Al 2 O 3 nanofillers content from 0.0 to 0.8 wt.% and slight decrease at 1.0 wt.%.…”
Section: Resultsmentioning
confidence: 99%
“…The tensile strength, Young’s modulus, and elongation at break initially increased and subsequently decreased as further addition of hybrid nanofillers to the XLPE matrix. It is reported in various studies that all samples of the nanocomposite have better tensile properties than unfilled XLPE [ 38 , 39 , 40 ]. This study ascertained an enhancement of tensile strength with increase in the LDH-Al 2 O 3 nanofillers content from 0.0 to 0.8 wt.% and slight decrease at 1.0 wt.%.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations regarding the AC and DC breakdown strength of thin polymeric films have already been observed and reported. 26,33 Further, the FTIR results revealed that the melting process of PU90 affected its physical characteristics, which influenced the AC characteristics of PU90 more than the DC characteristics. Overall, the breakdown strength of PU variants was low as compared to polyethylene and XLPE, 26,34 but it showed that increased hardness corresponds to higher dielectric strength.…”
Section: ■ Discussionmentioning
confidence: 98%
“…Figure 5 shows the SEM micrograph of PP/EPDM. In addition to fractography features [42], numerous isolated spots of EPDM (arrowed) were present within the blend material, indicating immiscibility between PP and EPDM [43,44]. A distinct boundary of two materials is evinced, indicating the absence of interfacial adhesion between PP and EPDM [27].…”
Section: Morphologymentioning
confidence: 97%